PERAN PEMERINTAH DESA DALAM MENINGKATKAN PERKEMBANGAN UMKM MASYARAKAT DESA GEDE PANGRANGO KECAMATAN KADUDAMPIT KABUPATEN SUKABUMI - Rosmiati, Neni; Sopyan , Iyan (CV. Era Digital Nusantara, 2024)
This study aims to analyze and describe the role played by the local government in the development of Micro, small and Medium Enterprises (MSMEs) in the area of Gede Pangrango Village, Kadudampit Disrict,Sukabumi Regency. MSMEs have an important role in the local and national economiy, as well as in creating jobs and increasing people’s income. Local governments have a significant role in providing support, regulation and facilitation for MSMEs growth. This research will analyze various policies, programs and initiatives taken by the regional government of Gede Pangrango village to support MSME development.